Trichomoniasis Among Females With Vaginal Discharge in Baghdad Medical City - Al-Kaisi, Aroub Abdul Rahman; Al-Janabi, Bahjat; Al-Tikriti, Raja (Journal of the Faculty of Medicine Baghdad, 2008)
Background:Trichomonas vaginalis is a pear shaped parasite, with a short undulating membrane, lined with a flagellum and four anterior flagella. It is one of the mostcommon organisms causing infection in the female genital tract, which is normally limited to vulva, vagina and cervix. It doesn't usually extend to the uterus. Themucosal surface may be tender, inflamed and covered with a frothy yellow or cream colored discharge.Aim:To evaluate the infection rate of Trichomonas vaginalis among females complaining of vaginal discharge with or without pruritis vulvae, and to isolate theparasite by different laboratory methods, such as wet mount method, culture on special media and staining by special stains e.g. Leischman's stain, Giemsa's stainand Papanicolaou's stain.Methods:The study was conducted in the period from November 1992 to August 1993 on 480 female patients presented with vaginal discharge with or without prurits vulvaeattended the Gynecological and Antenatal Outpatient Clinics in Medical City in Baghdad, compared to 50 females complaining of gynecological problems otherthan infection attended the same clinic. Investigations carried out during this work include: Wet mount examination ,Culture on artificial media ,Examination of fixed stainedsmears with: Gram’s stain , Leishman's stain ,Giemsa's stain, Papanicolaou's stained smear.Results:Among 480 females presented with vaginal discharge with or without pruritis vulvae, an infection rate of (19.16%) was reported. Females subjected to this studywere classified into different groups, non-diabetics, diabetics, workers in hospital and control group, giving an infection rates of (20.5%), (2.5%), (33.33%) and (8%)respectively. Evaluation of the rate of infection among different age groups revealed that the highest infection rate was in the ages of greatest sexual activitiesfrom (14-39) years old. The signs of Trichomonas vaginalis infection were those of vulvar, vaginal and cervical erythemae. The presenting symptoms were those ofdischarge, discharge & itching, discharge & dysuria, itching, discharge & itching & dysuria. However (12.5%) of the patients were asymptomatic. The discharge was ofdifferent characters and the patients presented in different stages of the disease. Conclusion:Trichomonas vaginalis is a common cause of vaginits , most frequently seen at the ages of greatest sexual activity where the patient usually presents with vaginaldischarge of different character which may or may not be associated with itching. It has been noticed that clinical judgement alone is unsatisfactory for thediagnosis of trichomoniasis and it must be aided by laboratory examination.